The Use of Information Technology to Enhance Management School Education: A Theoretical View - Leidner, Dorothy E.; Jarvenpaa, Sirkka L. (MIS Quarterly, 1995)
To use information technology to improve learning processes, the pedagogical assumptions underlying the design of information technology for educational purposes must be understood. This paper reviews different models of learning, surfaces assumptions of electronic teaching technology, and relates those assumptions to the differing models of learning. Our analysis suggests that initial attempts to bring information technology to management education follow a classic story of automating rather than transforming. IT is primarily used to automate the information delivery function in classrooms. In the absence of fundamental changes to the teaching and learning process, such classrooms may do little but speed up ineffective processes and methods of teaching. Our mapping of technologies to learning models identifies sets of technologies in which management schools should invest in order to informate up and down and ultimately transform the educational environment and processes. For researchers interested in the use of information technology to improve learning processes, the paper provides a theoretical foundation for future work.